The Effect of Principal Transformational Leadership, Work Climate, and Work Commitment on Teacher Performance in Public Elementary Schools in Pulau Petak Sub-District - Megawati Megawati; Ahmad Suriansyah; Sulistiyana Sulistiyana (MASI Mandiri Edukasi, 2026)
This study aims to describe and analyze the influence of transformational leadership of school principals, work climate, and work commitment on teacher performance in public elementary schools across Pulau Petak District. The research problem focuses on understanding how leadership and organizational factors influence teacher performance both directly and indirectly, with work commitment as a mediating factor, and the objective is to examine both direct and indirect effects among variables, highlighting the role of work commitment in mediating the relationship between leadership, work climate, and teacher performance. The research employed a quantitative approach using path analysis to test the hypotheses. Data were collected through questionnaires and analyzed using regression tests and Sobel tests. The findings reveal that (1) transformational leadership, work climate, work commitment, and teacher performance are all in the good category; (2) transformational leadership, work climate, and work commitment have direct effects on teacher performance; (3) transformational leadership and work climate have direct effects on work commitment; and (4) transformational leadership and work climate indirectly affect teacher performance through work commitment. These results indicate that teacher performance is influenced not only directly by leadership and work climate but also indirectly through work commitment, emphasizing the importance of transformational leadership and a supportive work climate in strengthening teachers’ commitment and enhancing their performance.